PENGARUH VARIABEL BUDAYA PERUSAHAAN TERHADAP KINERJA KELOMPOK PENERBITAN PERS JAWA POS - Ida Ayu Brahmasari (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2005)
The opportunities and threats occurring in the era of “press freedom” and “local government” effect the quality development of human resources of any press publishing company in Indonesia. Whether or not a corporate culture has been formalized and/or socialized throughout the organization, a corporate culture may characterize a press publishing company as it guides everyone’s behavior in the organization. Furthermore, a number of theories and previous researches showed that a corporate culture might effect on corporate performance.The objectives of this research are to examine the effects of organization values, organization climates, reward systems, and team orientation on performance of Jawa Pos press publishing group.284 respondents from 17 publishers of Jawa Pos press publishing group throughout the provinces of Bali, East Java, Central Java and Yogyakarta, participated in this study. The data were collected using questionnaires and analyzed using Structural Equation Modeling (SEM) analysis, which were processed using LISREL 8.30 version of statistic computer program. Results of this study proved that organization values, organization climates, as well as reward systems have significant effects on the performance of Jawa Pos press publishing group. Meanwhile, team orientation has insignificant effects on the performance of Jawa Pos press publishing group.The finding of this study is important empirical evidence on the development of organization behavior theories and practices.